BRAND EXPERIENCE UNTUK MEMPREDIKSI BRAND ATTITUDE PADA KONSUMEN SPORTING BRAND - JONATHAN WILSON CHANDRA; KENI KENI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to examine whether 1a) sensory brand experience, 1b) affective brand experience, and 1c) behavioral brand experience can predict behavioral brand attitude. 2a) sensory brand experience, 2b) affective brand experience, and 2c) behavioral brand experience can predict cognitive brand attitude. 3a) sensory brand experience, 3b) affective brand experience, and 3c) behavioral brand experience can predict affective brand attitude. Sample was selected using convenience sampling method and data were collected using online questionnaire. In total 260 participants responded the survey. The result of this study indicate that sensory brand experience can’t predict positively behavioral brand attitude. Affective brand experience can predict positively behavioral brand attitude. Behavioral brand experience can predict positively behavioral brand attitude. Sensory brand experience can predict positively cognitive brand attitude. Affective brand experience can predict positively cognitive brand attitude. Behavioral brand experience can predict positively cognitive brand attitude. Sensory brand experience can’t predict positively affective brand attitude. Affective brand experience can predict positively affective brand attitude. Behavioral brand experience can predict positively affective brand attitude.